Artificial Intelligence in Islamic Education (2018–2025): A Bibliometric Analysis of Research Trends and Collaboration - Hakiem, Marsekal Rahman (South Sulawesi Education Development, 2026)
Artificial Intelligence integration in Islamic education represents an emerging research domain gaining rapid scholarly attention. This bibliometric analysis examines the global research landscape on AI in Islamic Education from 2018 to 2025, utilizing the Scopus database and bibliometric analysis tools including VOSviewer and RStudio. Data retrieval was conducted on January 7, 2026. The study analyzed 29 articles from Scopus, identifying publication trends, research contributions by geographic location and institutions, citation patterns, and thematic clusters. Results reveal exponential growth with a 49.89% annual publication rate, concentrated primarily in Southeast Asia, with Indonesia and Malaysia accounting for 96.4% of global research output. Universitas Muhammadiyah Surakarta (Indonesia) and Malaysian Islamic universities emerged as leading research institutions. The research landscape is dominated by studies on AI applications in Qur'anic learning, pedagogical innovations, and technology acceptance among Muslim students, while critical research gaps remain in AI ethics, affective learning outcomes, and geographically contextualized implementation approaches. Citation analysis demonstrates a moderate impact (4.414 average citations per document) typical of newly established research fields. This analysis reveals that AI in Islamic Education has transitioned from nascent exploration to established scholarly priority within Muslim-majority regions, with substantial opportunities for international collaboration and evidence-based innovation to ensure AI technology serves Islamic education's ultimate mission of nurturing spiritually grounded and ethically upright learners.